2013
DOI: 10.4049/jimmunol.1300164
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus–Infected Cells Downregulate NKp30 and Inhibit Ex Vivo NK Cell Functions

Abstract: Hepatitis C virus (HCV) successfully evades the immune system and establishes chronic infection in ∼80% of cases. Immune evasion may involve modulating NK cell functions. Therefore, we developed a short-term assay to assess immediate effects of HCV-infected cells on ex vivo NK cytotoxicity and cytokine production. Natural cytotoxicity, Ab-dependent cell–mediated cytotoxicity, IFN-γ production, and TNF-α production were all significantly inhibited by short-term direct exposure to HCV-infected hepatoma–derived H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 74 publications
2
41
1
Order By: Relevance
“…88 Likewise, liver NK cells are impaired in function in HCV-infected individuals, 89 in part through HCV-mediated downregulation of NKp30. 90 HCV-infected cells can also inhibit NK cell cytotoxicity and cytokine production by expressing HCV-envelope that binds CD81 on NK cells, 91,92 or by HCV-core peptide mediated stabilization of HLA-E to inhibit NK cells through NKG2A. 93 In addition to interfering with NK cell receptor functions, certain viral proteins impact cytokine signaling as well, i.e., IL-10 homologs and IL-18 binding proteins.…”
Section: Nk Cell Activation and Persistence After Infectionmentioning
confidence: 99%
“…88 Likewise, liver NK cells are impaired in function in HCV-infected individuals, 89 in part through HCV-mediated downregulation of NKp30. 90 HCV-infected cells can also inhibit NK cell cytotoxicity and cytokine production by expressing HCV-envelope that binds CD81 on NK cells, 91,92 or by HCV-core peptide mediated stabilization of HLA-E to inhibit NK cells through NKG2A. 93 In addition to interfering with NK cell receptor functions, certain viral proteins impact cytokine signaling as well, i.e., IL-10 homologs and IL-18 binding proteins.…”
Section: Nk Cell Activation and Persistence After Infectionmentioning
confidence: 99%
“…Nattermann et al reported an increased expression of NKG2A/CD94 inhibitory receptors on circulating NK cells in patients with chronic HCV infection; however, in an in vitro model representative of acute HCV infection, neither NKG2A nor HLA-E expression increased on NK or HCV-infected cells, respectively [6769]. Nonetheless, to combat NK cell-mediated control of infection, HCV may employ multiple means of increasing expression of natural or decoy ligands for inhibitory NKRs as chronic infection develops and disease progresses.…”
Section: Natural Killer Cells In Hcv Infectionmentioning
confidence: 99%
“…Although no differences in NKG2C or NKG2D surface expression were noted, some in vitro experimental data suggested downregulated NKG2D and/or NKp30 surface expression after ex vivo exposure of NK cells to HCV-infected cells [68, 69]. Direct contact between NK cells and HCV-infected cells in vitro promotes downregulation of NKp30, suggesting that HCV can affect NK cell recognition and function through upregulation of an as yet unidentified ligand that physically interacts with NKp30 [69]. This possibility is supported by the demonstration of increased binding of recombinant NKp30 protein to HCV-infected Huh-7.5 cells [69].…”
Section: Natural Killer Cells In Hcv Infectionmentioning
confidence: 99%
“…IL-26 enhanced the cytotoxic activity of NK cells against the TRAIL-sensitive Jurkat (figure 5A) and Huh7.5 cell lines (figure 5B). Previous studies have reported that a short time contact with HCV-infected cells is sufficient to reduce the killing activity of NK cells against infected cells; this process, suspected to participate to HCV immune escape, can be reverted by NK cell activation 9 34. We thus analysed the ability of IL-26-stimulated NK cells to kill HCV-replicating Huh7.5 cells.…”
Section: Resultsmentioning
confidence: 99%